Pseudopotential-based study of electrical transport properties inherent to Bi-Ga alloys - Vora, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
In this paper, we account for the electrical transport properties of Bi-Ga alloys studied theoretically by employing our well-known model pseudopotential. The impact of various screening functions was studied using various exchange and correlation functions in the aforesaid investigation. The obtained results on electrical resistivity are found to be in qualitative agreement with the experimental data in the available literature.